Analysis of Storage Methods and Tarping Practices for Corn Stover Bales - Schon, Brittany N.; Darr, Matthew J.; Webster, Keith E.; Jennett, Nicole (Iowa State University Digital Repository, 2013)
In 2011 and 2012, Iowa State University conducted storage trials for large, rectangular corn stover bales to determine the most effective storage method for companies and farmers harvesting corn stover. Over 2000 bales were used for different storage trials, and five storage configurations were tested. Standard outdoor tarped and indoor stacks proved to be the most effective in preserving bale quality and limiting deterioration, with dry matter losses below 5% in 2012. Moisture content of the bales was studied by collecting pre and post-storage moisture contents of the bales. It was found that all bales, no matter the initial moisture content, would dry down to an industrial-acceptable moisture content of nearly 15%, if stored appropriately. Bale temperatures, which are an indicator of moisture content and microbial activity, were also studied to support the dry matter loss and moisture content data, as well as to ensure these stacks were not creating opportunities for bales to self-combust. In both years of temperature studies, no bales were found to reach temperatures near self-combustion level.